A TRANSDISCIPLINARY JOURNEY: COURSE CREATION AT A SOUTH AFRICAN UNIVERSITY - Taylor, Douglas; Schwaibold, Ute; Watson, Ingrid (European Scientific Journal, ESJ, 2015)
The paper reviews the process involved in developing a transdisciplinary Master’s degree in Global Change. It first considers the meaning of the various disciplinarities before reviewing the team selection and development process. It provides an overview of the research behind and development of the curriculum, and discusses dealing with academic administration. It finally provides an overview of the teaching experience. Lessons learned cover teams, their selection and development; structures and the work required to address administrative challenges; course design and the issue of transdisciplinarity; and teaching, including the use of various alternative teaching and learning methods are presented. This is followed by a postscript - an overview of a course module and students’ responses.